Restorative Legal Challenges of Abortion for Rape Victims in Indonesia - Renih Setiawan; Syarif Saddam Rivanie (Pandecta Research Law Journal, 2025)
Indonesia has provided leniency and exceptions to abortion for rape victims. The legalization of abortion is the fulfillment of the rights of rape victims to obtain abortion services as soon as possible by the requirements stipulated in the health law. In reality, the fulfillment of this right cannot be fully implemented. A challenge lies in the weak enforcement of the law. Indonesia has not firmly supported this rule. Victims have difficulty accessing abortion services. No regulation on emergency services regulates clearly and in a structured manner within the scope of the police or the scope of health organizations and victim protection organizations. In addition, the strengthening of the mentality of law enforcers and stakeholders has not been fully achieved. This study aims to explore the implications and factors that hinder access to abortion services for rape victims. The results of the study show that the factors that hinder access to abortion are due to weak law enforcement, weaknesses in the substance of the law, the complexity of laws and regulations, and the feeble mentality of the parties involved, so that slow handling results in the inability to implement abortion services for rape victims. To achieve the implementation of this abortion regulation, a national policy is needed within the scope of the police, policies in health organizations, and one-stop integrated service procedures. The urgency of this policy, apart from contributing to policy reform, is also important to make it easier for victims to get services without having to drain their energy, time, and costs. Based on this, Indonesia needs to take a more pragmatic, rational, integrated, and comprehensive approach through widespread socialization to the community, police, and other stakeholders.